Investigation of the Relationship between Antioxidant Levels and Body Mass Index and Obesity - Nurcan Kılıç Baygutalp; Özgür Araz; Ufuk Uzun; İlayda Havuz; Neslihan Yüce; Mehlika Alataş; Fatmagül Düzenli; Elif Zeynep Öztürk (Pharmata)
Objective: Today, it is well known that obesity plays a role in the pathogenesis of many diseases, and one of these mechanisms of action is oxidative stress. There are many studies on the formation of oxidative stress in obesity, but its effect on young adults (18-35 years old) is not fully known. Method: In this context, we investigated oxidative stress levels by measuring oxidant (MDA) and antioxidant (SOD) parameters in young adult obese and overweight individuals with ELISA method. Our hypothesis is that the oxidant parameter (MDA) is high and the antioxidant parameter (SOD) is low in young adult obese individuals due to oxidative stress. Results: According to the study results, a statistically significant difference was found in the SOD and MDA values ​​of overweight individuals (p